2011
DOI: 10.21101/cejph.a3629
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Practices in Jordanian People and their Impact on Semen Quality and Hormonal Levels among Adult Men

Abstract: Despite worldwide anti-smoking campaigns, cigarette smoking prevalence is increasing in the third-world countries. It is now regarded as the most important public health issue. Here, we study the current smoking situation and investigate the impact of cigarette smoking on semen quality and hormonal levels among adult people. Furthermore, we suggest various strategies to reduce smoking consumption among young individuals. A cross-sectional data from 804 adult smoker subjects (male n=530 and female n=274) aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Data from our results indicate that most infertile male were smoker 39(52%), that agreement with study of Al-Matubsi [54], and revealed significant low quality of sperm parameters in terms of semen volume, sperm count and motility in semen of infertile smokers. This finding is in accordance with those of some other studies [55,56,57].…”
Section: E-a Comparison Between Semen Parameters and Mda Among Fertilsupporting
confidence: 92%
“…Data from our results indicate that most infertile male were smoker 39(52%), that agreement with study of Al-Matubsi [54], and revealed significant low quality of sperm parameters in terms of semen volume, sperm count and motility in semen of infertile smokers. This finding is in accordance with those of some other studies [55,56,57].…”
Section: E-a Comparison Between Semen Parameters and Mda Among Fertilsupporting
confidence: 92%
“…Studies of the effect of tobacco use on testosterone and LH levels have been conducted mainly among adult males, with inconsistent results (Simon et al 1992;Field et al 1994;Svartberg et al 2003;Funabashi et al 2006;Al-Matubsi et al 2011). For instance, a study conducted by Richtoff et al examined the effect of tobacco use on reproductive factors among Swedish male adolescents (Richthoff et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is considered to be a risk to male infertility as it could be directly and indirectly toxic to spermatogenesis [4][5][6]. Even though the reason for the decline of semen quality remains unknown, the correlation between smoking and semen quality has been reported in many studies [7][8][9][10][11]. However, the effect of cigarette smoking on sperm quality reported by some studies was shown to be limited [12,13].…”
Section: Introductionmentioning
confidence: 99%